2018
DOI: 10.1177/0143034317752519
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stress on later literacy achievement via grit and engagement among dual language elementary school students

Abstract: The goal of this short-term longitudinal study was to identify how stress impacts later literacy achievement via the mediators of grit and emotional engagement. Study design included three time-points with students in 3rd through 5th grades who were lowincome, dual language learners in the US (N ¼ 142; 54% female; 75% Latina/o; M ¼ 9.47 years old). The measures were Time 1 student-reported perceived stress, Time 2 teacher-reported student grit and emotional engagement, and a Time 3 student literacy achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Researchers have explained that observers tend to rate their favorite targets more highly, particularly when test items are positive questions, such as positive emotions or characters (Jussim, ; Najman et al, ). Therefore, to avoid possibly inflated correlations, we decided to exclude teacher ratings (e.g., Alan, Boneva, & Ertac, ; Barrington, ; O'Neal, ) and parent ratings (e.g., Sturman & Zappala‐Piemme, ) of grit. Outcome measures were restricted to academic achievement, which was generally defined as the achievement of a particular result in a numerical grade in an assignment, exam, or degree within nonspecific subjects or GPA (Richardson, Abraham, & Bond, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have explained that observers tend to rate their favorite targets more highly, particularly when test items are positive questions, such as positive emotions or characters (Jussim, ; Najman et al, ). Therefore, to avoid possibly inflated correlations, we decided to exclude teacher ratings (e.g., Alan, Boneva, & Ertac, ; Barrington, ; O'Neal, ) and parent ratings (e.g., Sturman & Zappala‐Piemme, ) of grit. Outcome measures were restricted to academic achievement, which was generally defined as the achievement of a particular result in a numerical grade in an assignment, exam, or degree within nonspecific subjects or GPA (Richardson, Abraham, & Bond, ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have explained that observers tend to rate their favorite targets more highly, particularly when test items are positive questions, such as positive emotions or characters (Jussim, 1989;Najman et al, 2001). Therefore, to LAM AND ZHOU | 1657 avoid possibly inflated correlations, we decided to exclude teacher ratings (e.g., Alan, Boneva, & Ertac, 2016;Barrington, 2017;O'Neal, 2018) and parent ratings (e.g., Sturman & Zappala-Piemme, 2017) of grit.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…This study included variables collected at each of 3 time points over 4 months—teacher‐reported emotional engagement and teacher‐reported adapted grit in addition to a student performance literacy achievement task; these variables were part of a larger study (i.e., O'Neal, ; O'Neal et al, under review). Time 1 was collected from January to February 2014, Time 2 from March to April 2014, and Time 3 from May to June 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Still, the relationship between reading skills and a child's concurrent physiological stress level is not understood among the beginning readers in Grade 1. Considering older students and their self-reported stress, higher perceived stress is related to lower reading efficiency and comprehension during preadolescence (O'Neal, 2018). Adolescent students with reading disabilities experience more stress at school and a higher number of depressive symptoms (Undheim & Sund, 2008).…”
Section: Reading Skills and Stressmentioning
confidence: 99%